The Profile of Studentsâ Thinking in Solving Mathematics Problems Based on Adversity Quotient - Sari, Christina Kartika; Sutopo, Sutopo; Aryuna, Dyah Ratri (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this research was to know the thinking processes of climber, camper, and quitter high school students in solving mathematical problems. This research used a qualitative descriptive method. Subjects were determined by purposive sampling. The technique of collecting data was done by task-based interviews. Based on the results of data analysis it can be concluded that: (1) the profiles of climberâs thinking processes are: (a) assimilation and abstractionÂ in understanding problems, (b) assimilation, accommodation, and abstraction in planning problem solving (c) assimilation, accommodation, and abstraction in implementing the plan of problem solving, and Â (d) accommodation in checking the solution; (2) the profiles of camperâs thinking processes are: (a) assimilation in understanding mathematical problems, (b) assimilation, accommodation, and abstraction in planning problem solving, (c) abstraction in implementing the plan of problem solving, and (d) assimilation in checking the solution; (3) the profiles of quitterâs thinking processes are: (a) assimilation and abstraction in understanding problems, (b) assimilation, accommodation, and abstraction in planning problem solving, (c) assimilation, accommodation, and abstraction in implementing the plan of problem solving, and (d) assimilation in checking the solution.